Examining Duffy’s textual space in “Water” and “Cold” through the unnatural ecopoetics concept - Abdulkadhim Mhana, Zainab; Talif, Rosli; Zainal, Zainor Izat; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2020)
Unnatural ecopoetics presents new directions for poetry scholars. It is a theoretical lens that studies how texts use self-reflexive language and formal experimentation to create a textual space where material and nonmaterial environmental elements are uncovered. The term material stands for all physical objects and places, whether man-made or occurring naturally in the world. Nonmaterial, on the other hand, refers to the invisible emotional, historical, political, and personal elements that influence the speaker’s experience of space and the translation of it to the textual space of a poem. Post-modernist poet Carol Ann Duffy has played a pivotal role in contemporary English poetry. While many studies have dealt with her poetry, few have examined Duffy’s poetry in light of the unnatural ecopoetics concept. In this paper, the reader is invited to read within the textual space of Duffy’s “Water” and “Cold” (2011) through the lens of unnatural ecopoetics. This article argues that Duffy’s experience and memories of her mother’s last days configured nonmaterial elements fused with material elements of her environment. The findings of this study provide a new way of analysing contemporary poetry through ecopoetics reading by delving into literary texts and examining all the environmental elements and situations around a persona in a poem or the poet.